A vida exterior das fachadas: fotos e desenhos da rua Crémieux desde o Instagram: The Crémieux street in pictures and drawings: the exterior life and its presentation on Instagram (Simbiótica. Revista Eletrônica, 2023)
The first part of this work is dedicated to the question of the life of facades, that seems to be an incongruence that follows indefinitely among specific histories and persistent appearances. The second part experiments with drawing as a mode of encountering the precarious ways by which the profusion of images of the facades from Crémieux street brings with them the limit of an “exterior life” (BRUNO, 2013), going for the search of chance and necessity that mark the way that they are presented as being, also, specific.